The Development of E-catalog of Seed Plants based on Mini Research in Semirang Tourism Area as a Supplement to Learning Plantae in Senior High Schools - Yulalifah, Lilif; Ngabekti, Sri (FMIPA UNNES, 2020)
Semirang tourism area has natural potential that can be utilized as a source of learning, one of which is seed plants. The Semirang area is located in Gogik Village, West Ungaran District, Semarang Regency with an altitude above 700 meters above sea level. Seed plants have important values for humans and the environment, among others; economic, aesthetic, educational, endemic, conservation, and cultural values. This study aims to identify the richness of the species of seed plants in the Semirang tourism area as a learning supplement for Plantae material in High School. This study was designed with a modified Research and Development (R&D) method. The results of the identification of seed plants in the Semirang tourism area recorded 88 species of seed plants which are divided into 5 divisions, 6 classes, 32 orders, and 48 families dominated by angiosperm. The precentage of gymnosperms is 5.68% and the precentage of angiosperms is 94.32%. E-catalog of seed plants that has been developed has obtained very suitable criteria for supplementing plantae material in class X-Matematics and Natural Sciences students. The result of the acquisition of 85.83% of material experts (V1); 97.81% of media experts (V2); and 73.50% of media experts (V3). Teacher responses received a score of 97.91%, student responses to the e-catalog obtained a precentage of 83.50% and student responses regarding attitudes of concern for plant preservation gained a precentage of 85.00%.